Ectopic Lymphoid Follicle Formation and Human Seasonal Influenza Vaccination Responses Recapitulated in an Organ‐on‐a‐Chip. Issue 14 (14th March 2022) - Goyal, Girija; Prabhala, Pranav; Mahajan, Gautam; Bausk, Bruce; Gilboa, Tal; Xie, Liangxia; Zhai, Yunhao; Lazarovits, Roey; Mansour, Adam; Kim, Min Sun; Patil, Aditya; Curran, Danielle; et al.
Abstract: Lymphoid follicles (LFs) are responsible for generation of adaptive immune responses in secondary lymphoid organs and form ectopically during chronic inflammation. A human model of ectopic LF formation will provide a tool to understand LF development and an alternative to non‐human primates for preclinical evaluation of vaccines. Here, it is shown that primary human blood B‐ and T‐lymphocytes autonomously assemble into ectopic LFs when cultured in a 3D extracellular matrix gel within one channel of a two‐channel organ‐on‐a‐chip microfluidic device. Superfusion via a parallel channel separated by a microporous membrane is required for LF formation and prevents lymphocyte autoactivation. These germinal center‐like LFs contain B cells expressing Activation‐Induced Cytidine Deaminase and exhibit plasma cell differentiation upon activation. To explore their utility for seasonal vaccine testing, autologous monocyte‐derived dendritic cells are integrated into LF Chips. The human LF chips demonstrate improved antibody responses to split virion influenza vaccination compared to 2D cultures, which are enhanced by a squalene‐in‐water emulsion adjuvant, and this is accompanied by increases in LF size and number. When inoculated with commercial influenza vaccine, plasma cell formation and production of anti‐hemagglutinin IgG are observed, as well as secretion of cytokines similar to vaccinated humans over clinically relevant timescales. Abstract : Primary human lymphocytes taken from blood are reprogrammed into lymphoid follicles (LF) by superfusion in an organ chip device. These ectopic LFs express AID and can be induced to form plasma cells and antigen‐specific antibodies upon activation with different stimuli including adjuvants and seasonal influenza vaccines.